Socio-emotional Development and Coping Mechanisms of Selected Pantawid Pamilyang Pilipino Program Families during the Covid-19 Pandemic - Marinel A Dugan; Rebecca Rosario O Bercasio; Shieralyn B Villar; Nathania Fane B Nuelan (Randwick International of Education and Linguistics Science Journal, 2023)
Families find various ways to adjust to the consequences brought by the COVID-19 pandemic, the new normal setting. While the Pantawid Pamilyang Pilipino Program beneficiaries, until then, experienced tremendous problems in securing a job and stable income, and now their situations are aggravated by the pandemic. This study aimed to determine the: (1) profiles; (2) challenges encountered; (3) socio-emotional development (perceived effects of the pandemic on attitudes, emotions, and socialization); and (4) coping mechanisms and suggestions of the Pantawid Pamilyang Pilipino Program family beneficiaries in Sagpon, Daraga, Albay to overcome their socio-emotional changes. The researchers visited and assisted 10 Pantawid Pamilyang Pilipino Program families in answering the survey questionnaire with minimum health protocols observed. Key informant interviews were also conducted with 5 consenting families to collect more data on their experiences and coping mechanisms. The responses from the survey questionnaire were analyzed and interpreted using statistical tools and thematic analysis, while data from the key informant interviews used the case study method. The results revealed that the participants disagreed that they perceived the effects of the pandemic on their attitudes and emotions. In socialization, they believed that it is true to some extent that they experienced some changes. Among their perceived effects of the pandemic on their socio-emotional development were symptoms of hypochondriasis, anxiety, paranoia, and introversion. As coping mechanisms, they suggested praying, meditating, and doing collective hobbies with the family. An intervention is recommended to help the participants with their socio-emotional difficulties.